The Impact of Donald J. Trump’s Egocentric Policies on Indonesia: A Neorealist Analysis (Case Study: The 2024–2025 Trade War) - SEPTIAWAN, YUDI; Jamal, Din Aulia; Muhammad, Amir Yusuf; Endah, Kurniati (The Department of International Relations Universitas Mataram, 2025)
This study analyses the impact of the United States' foreign policy under Donald Trump on Indonesia, with particular attention to the trade war during the 2024–2025 period. Utilizing a Neorealist theoretical framework, the analysis highlights the significance of national interests, global power distribution, and international system dynamics in shaping bilateral relations. The